1996
DOI: 10.1007/bf00114860
|View full text |Cite
|
Sign up to set email alerts
|

Defining elder mistreatment in four ethnic groups across two generations

Abstract: Ethnic and generational variation in elder mistreatment has only recently been explored. This research builds upon pioneer work in the field by examining perceptions of elder mistreatment across four ethnic groups (European-American, African-American, Puerto Rican, and Japanese-American) and two generations (elder and 'baby boom' caregiver). Focus group discussions revealed differences in defining elder mistreatment and responding to it. They also suggested that psychological abuse and neglect may be more impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 26 publications
(30 reference statements)
7
47
0
Order By: Relevance
“…One in 6 professional caregivers reported committing abusive acts but over four-fifths observed it. Unfortunately, only 7 of the studies that were reviewed used measures for which any type of reliability and validity had been assessed Americans view acts like "silence treatment" or yelling at the older adult more harshly than non-Asian Americans (e.g., Anetzberger, Korbin, & Tomita, 1996). In addition, foreign-born Asians seem to view such acts even harsher than American-born Asians (e.g., Moon, Tomita, & Jung-Kamei, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…One in 6 professional caregivers reported committing abusive acts but over four-fifths observed it. Unfortunately, only 7 of the studies that were reviewed used measures for which any type of reliability and validity had been assessed Americans view acts like "silence treatment" or yelling at the older adult more harshly than non-Asian Americans (e.g., Anetzberger, Korbin, & Tomita, 1996). In addition, foreign-born Asians seem to view such acts even harsher than American-born Asians (e.g., Moon, Tomita, & Jung-Kamei, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, elder abuse studies tend to contain only a small number of items relating specifically to financial abuse, and therefore their results should be interpreted cautiously. On this background, various studies do suggest that there are different cultural, social, familial, and generational expectations and attitudes about appropriate financial transactions within families (Anetzberger, Korbin, & Tomita, 1996;Daskalopoulos, Kakouros, & Stathopoulou, 2007;Daskalopoulos, Mullin, Donovan, & Suzuki, 2006;Helmes & Cuevas, 2007;Hudson & Carlson, 1998;Mercurio & Nyborn, 2006;Moon, Tomita, & Jung-Kamei, 2001;Moon & Williams, 1993;Sanchez, 1996;Tsukada, Saito, & Tatara, 2001).…”
Section: Individual and Community Attitudesmentioning
confidence: 96%
“…A study in Israel found that the Ashkenazi sample stressed physical and economic abuse as forms of moderate abuse, and neglect and disrespect as forms of mild abuse, more than the Sephardic sample did (Rabi, 2006). Also, Anetzberger et al (1996) found differences in perceptions of elder abuse across four ethnic groups in the USA. No study assessing these differences among nursing aides could be identified.…”
Section: Introductionmentioning
confidence: 93%
“…Cultural factors may affect the views of diverse ethnic populations as to what constitutes abuse (Moon and Williams, 1993;Anetzberger et al, 1996), yet few studies have examined how cultural groups differ in their attitudes to it (e.g. Moon and Williams, 1993;Anetzberger et al, 1996;Tam and Neysmith, 2006).…”
Section: Introductionmentioning
confidence: 99%